Ultrasound in phage display: a new approach to nonspecific elution - Mojca Lunder; Tomaž Bratkovič; Uroš Urleb; Samo Kreft; Borut Štrukelj (BioTechniques)
Libraries of phage-displayed random peptides are routinely used to identify target-binding peptides. Phages are commonly eluted in a nonspecific manner, especially if there are no available ligands of the particular target to use as competitors. However, the present study clearly demonstrates that nonspecific elution is not always able to break peptide-target interactions. To circumvent this we have developed an improved nonspecific elution strategy that uses ultrasound to release target-bound phages and enables selection of high-affinity clones in a single step.